The Implementation of Social Studies Learning in the Independent Learning Curriculum at SMP Negeri 2 Pontianak - Nurhesti, Nurhesti; Venny Karolina; Hadi Wiyono; Maria Ulfah; Iwan Ramadhan (STKIP Taman Siswa Bima, 2024)
The research was conducted to understand the implementation of Social Studies (IPS) teaching in the Independent Learning curriculum at SMP Negeri 2 Pontianak. This research used a qualitative method, with data collection techniques involving field observations, interviews (with IPS subject teachers, curriculum vice principals, and students), and documentation. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The results of this research indicate that: (1) The implementation of IPS teaching in the Independent Learning curriculum at SMP Negeri 2 Pontianak involves the use of teaching modules in the IPS learning process. The designed teaching modules are tailored to the components of the teaching modules, meeting the needs of the students. Various teaching methods are used, including group discussions in the form of mind mapping and practical activities. (2) Challenges in implementing IPS teaching in the Independent Learning curriculum at SMP Negeri 2 Pontianak include the unattractive content of the platform, a lack of guidance for developing teaching modules, limited time for preparing various teaching methods, and a shortage of reading materials. (3) Efforts made to address the challenges of implementing IPS teaching in the Independent Learning curriculum at SMP Negeri 2 Pontianak include searching for online references related to teaching modules, creating a timeline for developing various teaching methods, and searching for reading materials on the internet related to the Independent Learning curriculum, as well as participating in Independent Learning curriculum training.